Optimasi Formula Spray Gel Ekstrak Bawang Tiwai (Eleutherine americana (Aubl) Merr) - Maulidya Maulidya; Fika Aryati; Yurika Sastyarina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
The ethanolic extract from the bulb of Eleutherine americana has the potential for anti-inflammatory activity to be developed into a preparation that is a practical spray gel to use. The aim of this study is to made a spray gel containing ethanolic extract from the bulb of Eleutherine americana. Spray gel preparation was prepared by varying the concentration of Carbopol as a gelling agent with a concentration of F1 (0.4%), F2 (0.6%), and F3 (0.8%) with active substances and evaluated physical stability. Data from the results of physical stability testing in statistical analysis. Organoleptic test results and homogenity of ethanolic extract from the bulb of Eleutherine americana spray gel from all formulas showed stable, pH was in the range of 5.2-6.1 and Viscosity in formulas 1, 2, and 3 were respectively 0.65-1323 (Pa.s ) this condition is still within the range of viscosity of spray gel formulation, and have a spread pattern. While the formula 2 and 3, the viscosity is not eligible.